Clash or alliance - Nina-Birke Glonnegger (Politikon, 2008)
Huntington's "Clash of Civilizations" theory gained new topicality through actual events in the political world climate against the background of 9/11 and the wars in Iraq and Afghanistan. Along with those conflicts, Huntington's theses seem to be more current than ever before and became the focus of the public discourse, in which - it seems - the gap between supporters and adversaries gets bigger every day. This article aims to evaluate his theory within the context of actual political events in the field of international relations. The empirical attempt of this study will be the presentation and evaluation of conflict statistics regarding the conflict climate in the years 2000 and 2006 in order to confirm or disprove several aspects of the clash of civilizations hypothesis.